Creative Thinking Profile of Senior High School Class X Students in Mathematics Problem-Solving in Reviewed of Adversity Quotient - Rafiqa, Shara; Rochaminah, Sutji; Rizal, Muh. (Jurnal Riset Pendidikan MIPA, 2019)
This study aims to obtain a description of the profile of creative thinking of class X high school students in solving mathematical problems in terms of Adversity Quotient (AQ). The subjects of this study were high school students of class X who had AQ with quitter type (SQT), camper (SCP), and climber (SCB). Data collection used test methods, methods of thinking, interviews, and observation. The results of this study are: a) SQT showes the existence of fluency and flexibility in the answer, namely by writing different ways and there were ways with the same pattern. The ways that he used were new ways for her which means that SQT has a novelty in solving problems. b) SCP also showed fluency, flexibility and novelty. The two ways he given were different from the other subjects, there were answers with the same pattern, and the method used was an unusual method. c) SCB showed excellent fluency and flexibility through the three ways he used it to solve problems. All the ways that he used were new ways for her, and he is willing to solve any problems after the problem.